2015
DOI: 10.1080/10495142.2015.1011511
|View full text |Cite
|
Sign up to set email alerts
|

Small Business–Nonprofit Collaboration: Locally Owned Businesses Want to Take Their Relationships With Community-Based NPOs to the Next Level

Abstract: This two-part, mixed-methods study explored how and why small businesses engage in both philanthropic and transactional partnerships with community-based nonprofits (NPOs), and what business owners expect from their nonprofit partners. Findings from focus groups and a survey indicate that U.S. small businesses (a) are interested in a higher representation on nonprofit boards; (b) are more likely to support NPOs that focus on the local community's needs; and (c) seek long-term, committed partnerships with NPOs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 27 publications
(58 reference statements)
1
10
0
Order By: Relevance
“…The interviewees also referred to, as a criterion to consider when choosing the NPO to donate to, physical proximity. These results reinforce the assumptions of the existing literature (Sargeant and Woodliffe 2007;Zatepilina-Monacell 2015). Fifteen interviewees out of 20 reported that they preferred to donate to local NPOs: "If we have a community closer needing support, we help more quickly, we know their stories and it is easier to follow the interventions and results of action" (Interviewee 7); "I make donations more quickly to closer institutions, because I can see their performance closely" (Interviewee 5); "Companies have social obligation to help the geographical area in which they are inserted, because we are part of the evolution and the growth and we take on the local resources" (Interviewee 4).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The interviewees also referred to, as a criterion to consider when choosing the NPO to donate to, physical proximity. These results reinforce the assumptions of the existing literature (Sargeant and Woodliffe 2007;Zatepilina-Monacell 2015). Fifteen interviewees out of 20 reported that they preferred to donate to local NPOs: "If we have a community closer needing support, we help more quickly, we know their stories and it is easier to follow the interventions and results of action" (Interviewee 7); "I make donations more quickly to closer institutions, because I can see their performance closely" (Interviewee 5); "Companies have social obligation to help the geographical area in which they are inserted, because we are part of the evolution and the growth and we take on the local resources" (Interviewee 4).…”
Section: Resultssupporting
confidence: 92%
“…Only 3 interviewees pointed out the positive financial return to the company, but all admit an intangible positive result the businesses get in awareness and positioning. This result emphasises that the local community is a lever to raise reputation and networking, contrasting with the answers about the solely altruistic motivation to donate Zatepilina-Monacell 2015).…”
Section: Resultsmentioning
confidence: 73%
“…Whereas our thesis is that small local businesses have the most potential for providing crime reduction, it is also possible that larger local businesses may provide some more limited crime reduction potential. For example, the non-profit organization (NPO) literature has suggested that locally owned businesses are willing to financially and socially support local NPOs that focus on the local community's needs and establish a longer-term relationship with them to jointly address community problems (Austin 2000;Cho and Kelly 2013;Zatepilina-Monacell 2015). Specifically, Austin (2000) conceptualized the three stages of partnership between NPOs and local businesses: 1) philanthropic (businesses financially support the partner NPOs through charitable donations); 2) transactional (businesses and NPOs jointly pursue a mutually beneficial relationship); and 3) integrative (businesses and NPOs share their common missions and collaborate to support common societal good for the local community).…”
Section: The Impact Of Large Local Businesses On Crimementioning
confidence: 99%
“…Consequently, due to the informal nature of CSR in SMEs, nonprofits may be less aware of SMEs' community involvement practices, which could hinder business-nonprofit partnerships. Indeed, a study of the corporate community involvement practices of American SMEs found that representatives expressed interest in establishing more sustainable, mutually beneficial partnerships with nonprofits, but they perceived a lack of requests for support or interest from nonprofits (Zatepilina-Monacell, 2015). Moreover, little is known about the specific manifestations of ESV within SMEs, or how different stakeholder groups (e.g., employees, employers, nonprofit representatives) perceive and understand it.…”
Section: The Case Of Small and Medium Enterprisesmentioning
confidence: 99%